How the City of London works : an introduction to its financial markets - Clarke, William M. (London : Sweet and Maxwell ltd, South Quay plaza Formerly waterlow publishers, 1991)
The book attempts to explain quite simply what goes on in the financial markets of the City of London and how each of them works.
gau 05/08/16
Loans
Keywords: Financial markets; Financial institutions; London